673 A multi-disciplinary, inter-continental collaboration to build capability in occupational health among health care professionals. (24th April 2018) - Naik, Inakshi; Mittal, Ashish; Danielson, Tor; Nicholas, Robin; Seneviratne, Mahinda
Abstract : Introduction: The interaction between community, environment and the workplace is crucial in the provision of basic health care services in low resource countries. United Nations' Sustainable Development Goals, strategies of its agencies WHO and ILO and professional bodies such as ICOH and IALI have highlighted the need for capability building and integration in delivering the necessary services to these communities. However, health care professionals, including medical doctors and nurses undergo limited training in occupational health during their professional undergraduate education. Methods: A series of workshops for health care professionals to develop knowledge and basic skills in workplace hazard identification, assessment and control were conducted in India and Malaysia. The multi-disciplinary program involving occupational medicine, hygiene, ergonomics and hazard communication was delivered by a group of occupational health professionals from five different continents. Their time and resources were provided voluntarily at no cost for the local organisers. Result: The workshops involved interactive group work facilitated by skilled specialists sharing their international experiences, together with demonstration of case studies by local experts. This approach enabled the diverse local health care workers, especially young females, to share the challenges faced in their work and develop valuable skills that can be applied to their work. Discussion: The success of these workshops has inspired the volunteers to explore the potential for developing a more sustainable 'academy' for capability building in basic occupational health. This model for a social enterprise in low resource countries through collaborating at international level will be presented and discussed.